Religious Sociological Approach to Social Change in Revelation Period: The Circular Loop Approach/Vahiy Dönemi Sosyal Değişmeye Din Sosyolojik Yaklaşım: Dairesel Döngü Yaklaşımı - Ali Akdoğan (İslam Medeniyeti Araştırmaları Dergisi, 2015)
Since foundation of sociology of religion, many subjects have been examined with this regard and one of the most important subject is religion and social change relations. Sociology of Religion has placed special emphasis on examination of social change subject since mid of twentieth century, examination of social change process has taken up a lot of room in religion sociology literature of the last fifty years. Social change which is one of the important study fields of sociology necessitates the presentation of models to be explained. Whereas models may differ from society to society. As each societal structure has characteristics of its own, taking a model as an example may not provide an explanation of the social change in that society. What needs to be done in this situation is to exemplify the principles of a new model, a new denotation and model. This article is a social change model study to put forth relation between religion and social change and it comprises 23 years of Muhammad The Prophet. The change which occurred in the society in 23-years period which is referred to as the revelation period in the article has been explained through the circular loop model and the principles of this model has been stated conceptually.